The reluctance among women customers towards internet banking / Haryana Hidayah Mohd Aris - Mohd Aris, Haryana Hidayah (Faculty of Business and Management, 2010)
Internet Banking has provided an opportunity for banking institutions to introduce new services to the consumer. The facilities provided enhanced functionalities and simple navigation, make Internet Banking easy and give more reasons to consumer to bank online. Somehow, these advanced technologies come with its cons which draw refusal among some of the consumer to adopt it. This research is made to study and find out the factors that determine the reluctant of using Internet Banking among customers as a new way in conducting payment transactions. From the result of the study, the independent variables are usage barrier, value barrier, risk barrier, tradition barrier, and image barrier. All the independent variables are the factors that determine the reluctant towards Internet Banking among customers. The research methodology used to gather the information is the secondary data, interviews and many others. The findings of this research is to answer whether the independent variables are effectives or ineffective to determine the reluctant towards internet banking.